Extracorporeal cardiopulmonary resuscitation after out‐of‐hospital cardiac arrest in a Danish health region. Issue 2 (9th December 2016) - Fjølner, J.; Greisen, J.; Jørgensen, M. R. S.; Terkelsen, C. J.; Ilkjær, L. B.; Hansen, T. M.; Eiskjær, H.; Christensen, S.; Gjedsted, J.
Abstract : Background: Extracorporeal Cardiopulmonary Resuscitation (ECPR) has emerged as a feasible rescue therapy for refractory, normothermic out‐of‐hospital cardiac arrest (OHCA). Reported survival rates vary and comparison between studies is hampered by heterogeneous study populations, differences in bystander intervention and in pre‐hospital emergency service organisation. We aimed to describe the first experiences, treatment details, complications and outcome with ECPR for OHCA in a Danish health region. Methods: Retrospective study of adult patients admitted at Aarhus University Hospital, Denmark between 1 January 2011 and 1 July 2015 with witnessed, refractory, normothermic OHCA treated with ECPR. OHCA was managed with pre‐hospital advanced airway management and mechanical chest compression during transport. Relevant pre‐hospital and in‐hospital data were collected with special focus on low‐flow time and ECPR duration. Survival to hospital discharge with Cerebral Performance Category (CPC) of 1 and 2 at hospital discharge was the primary endpoint. Results: Twenty‐one patients were included. Median pre‐hospital low‐flow time was 54 min [range 5–100] and median total low‐flow time was 121 min [range 55–192]. Seven patients survived (33%). Survivors had a CPC score of 1 or 2 at hospital discharge. Five survivors had a shockable initial rhythm. In all survivors coronary occlusion was the presumed cause of cardiac arrest. Conclusion: Extracorporeal cardiopulmonary resuscitation is feasible as a rescue therapy in normothermic refractory OHCA in highly selected patients. Low‐flow time was longer than previously reported. Survival with favourable neurological outcome is possible despite prolonged low‐flow duration.